Evaluation of Physical Properties of Selected Excipients for Direct Compressible Tablet - Rahman, SM Moshiur; Saha, Tushar; Masum, Zia Uddin; Chowdhury, Jakir Ahmed (Bangladesh Pharmaceutical Journal, 2017)
Excipients play important roles in the manufacturing of direct compressible tablet. The physical properties of excipients like flow properties, bulk density, tapped density, compressibility and diameter of particles are the most important studies which should be taken under consideration. Excipients like lactose, ludipress, avicel, povidone, sodium starch glycolate, sodium lauryl sulfate, sodium carboxy methyl cellulose, polyethylene glycol 4000 (PEG 4000) and maize starch are used and found that PEG 4000, avicel PH-101, ludipress and sodium lauryl sulfate showed an angle of repose below 400 which indicates good flow properties and others are not. The highest compressibility value is obtained from lactose and compressibility value was lowest for PEG 4000. It was found from the average diameter of excipients that sodium starch glycolate is very fine graded powder because all particles pass through a sieve (100 mesh) and the highest value is obtained from PEG 4000. Bangladesh Pharmaceutical Journal 20(1): 34-38, 2017